2009
DOI: 10.1007/s12562-009-0059-3
|View full text |Cite
|
Sign up to set email alerts
|

Pinger affects fish catch efficiency and damage to bottom gill nets related to bottlenose dolphins

Abstract: There is some evidence that the presence of Tursiops truncatus in fishing areas represents a real economic threat to fishermen due the dolphin feeding on the entangled fish, damaging the nets and reducing the fish catch. We have carried out experiments to assess the efficiency of a pinger in decreasing the interaction between the dolphins and fishing nets, in a fishing area off the coast of southern Italy, where Tursiops truncatus is frequently observed to interact with bottom gill nets. Two identical monofila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…Considerable money and effort has been invested in attempts to reduce bycatch [76]–[79], which is a problem for many cetacean populations around the world [78],[80], including the Danish harbour porpoise [35]. Most efforts have focused on acoustic deterrent devices (ADDs) or “pingers”, which produce sounds that are supposed to deter cetaceans from approaching nets.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable money and effort has been invested in attempts to reduce bycatch [76]–[79], which is a problem for many cetacean populations around the world [78],[80], including the Danish harbour porpoise [35]. Most efforts have focused on acoustic deterrent devices (ADDs) or “pingers”, which produce sounds that are supposed to deter cetaceans from approaching nets.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic device (ADD = Acoustic Deterrent Device named also pingers and AHD = Acoustic Harassment Device) is the mostly used measure to mitigate toothed whale depredation occurring in various fisheries, from longlines to gillnets (Bordino et al, 2002;Buscaino et al, 2009;López and Mariño, 2011;Mooney et al, 2009;Reeves et al, 1996). Longlines due to their length are almost impossible to protect efficiently with AHD.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, there are issues of low statistical power in some studies (e.g. Gazo et al 2008, Buscaino et al 2009), but observed reductions are not consistently significant or of substantial economic benefit. Perhaps most telling is the fact that we are unaware of any case in which fishermen have voluntarily adopted and continued the use of acoustic pingers to reduce depredation, although it is certainly true that fishermen have experimented with such devices outside formal experimental settings.…”
Section: Use Of Pingers To Reduce Depredationmentioning
confidence: 99%
“…In general, experiments have demonstrated a small reduction in the damage to nets (reflected in the number of holes, for example) and increases in fish catches when acoustic pingers are employed (Northridge et al 2003, Brotons et al 2008b, Gazo et al 2008, Buscaino et al 2009). Several other issues limit our ability to draw broad conclusions from this work, including the existence of numerous other marine predators (sharks, turtles and other fishes) that engage in depredation, and the fact that some fish lost to depredation are removed completely, i.e.…”
Section: Use Of Pingers To Reduce Depredationmentioning
confidence: 99%